Use of embolization of the middle meningeal artery in chronic subdural hematoma recurrence - Vargas-Urbina, John F. (2020)
Chronic subdural hematoma (CSDH) is a frequent neurosurgical condition, which may develop recurrence in up to 30% of all cases. Embolization of the middle meningeal artery (MMA) is an adjuvant management strategy for reducing recurrence, especially in patients with risk factors, and it has a low complication rate. We present the case of an 83-year old male with history of anticoagulation, who was admitted in a healthcare facility because of right hemiparesis, dysarthria and gait impairment, and he had been sick for one week. A trepanation and CSDH evacuation were uneventfully performed. One month later, the patient was brought back because of CSDH recurrence, so another trepanation and adequate CSDH evacuation were performed, followed by embolization of the ipsilateral MMA. A control assessment after two months revealed absenceof recurrence and neurological improvement. We conclude that MMA embolization was an efficacious adjuvant therapy aiming to reduce CSDH recurrence, and this procedure may be indicated in patients with risk factors for recurrence.